Pulsos láser de femtosegundo en espectroscopía y microscopía de dos fotones - Coello, Yves (2008)
Femtosecond laser pulses in two-photon spectroscopy and microscopy: The application of shaped ultrashort laser pulses (?10fs) in two-photon spectroscopy and microscopy carried out in our group is  described, highlighting the advantages and requirements of this approach. In addition, a brief description of pulse shaping, phase distortions experienced by femtosecond laser  pulses and how to correct these distortions using a pulse shaper is also presented.